Study of Literature: The Role of Traditional Games as a Learning Media to Instill Character Education in Elementary School Students - Miratunnisah, Miratunnisah (MANDALIKA : Journal of Social Science, 2024)
Traditional games are games owned by a group of people, where in these games they adhere to the norms and customs of the community passed down from their ancestors to the next generation. The aim of this research is to describe the role of traditional games as interactive learning media to instill character education in elementary school students. Character education contained in traditional games contains the values ​​of honesty, enthusiasm, good manners, responsibility, cooperation, discipline, hard work, helping each other, never giving up and so on. The methods used in this research are literature study, searching, analyzing and drawing conclusions. And the results obtained in this research show that traditional games can instill character education, for example religion, honesty, enthusiasm, good manners, responsibility, cooperation, discipline, sportsmanship, hard work, mutual help, never giving up and many more. Therefore, it is important to re-instill traditional games for children as a learning medium that can build good character in children